Inhibition of Cyclin-Dependent Kinase 2 by the Chk1-Cdc25A Pathway during the S-Phase Checkpoint Activated by Fludarabine: Dysregulation by 7-Hydroxystaurosporine - Sampath, Deepa; Shi, Zheng; Plunkett, William (Molecular pharmacology, 2002)
Human myeloid leukemia ML-1 cells responded to cytostatic concentrations of fludarabine nucleoside (F-ara-A) by instituting an arrest in S-phase that involved the inhibition of cyclin-dependent kinase 2 (Cdk2). This seemed to be mediated by 1) persistent phosphorylation on the Tyr15 residue of Cdk2 and 2) an increased association of Cdk2 with p21. S-phase arrest was also associated with an increase in Chk1 kinase activity. Concomitantly, the activity of Cdc25A phosphatase was decreased. Immunoprecipitation studies demonstrated complexes of Cdk2, Cdc25A, and Chk1. The addition of the Chk1 kinase inhibitor 7-hydroxystaurosporine (UCN-01) to F-ara-A–arrested S-phase cells resulted in a rapid decrease in the fraction of cells with an S-phase DNA content and a corresponding increase in the fraction of apoptotic cells. Under these conditions, the kinase activity of Chk1 was reduced, Cdc25A phosphatase activity was increased, the level of Tyr15 phosphorylation of Cdk2 was reduced, and the kinase activity associated with immunoprecipitates of Cdk2 and cyclin A was reactivated. UCN-01 also had no effect on the association of p21 with Cdk2. Lastly, cells incubated with UCN-01 before F-ara-A addition did not arrest in S-phase. Thus, the DNA damage induced by F-ara-A initiated a hierarchical regulatory cascade through Chk1 and Cdc25A that resulted in Cdk2 inhibition, affecting an S-phase checkpoint that was dysregulated by UCN-01. These results suggest a mechanism by which UCN-01 enhances the cytotoxicity of agents that cause an S-phase arrest.